2017
DOI: 10.1902/jop.2016.160193
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Aggregatibacter actinomycetemcomitans Leukotoxin‐Neutralizing Antibodies in Periodontitis

Abstract: Presence and levels of systemic immunoreactivity against A. actinomycetemcomitans Ltx are associated with decreased remission after otherwise successful periodontal treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…All antibody levels were remarkably stable during the 6‐month periodontal treatment. This has also been observed in other studies, whether comprising treatment or not . The levels of antibody to A. actinomycetemcomitans and P. gingivalis are determined primarily by the presence of the bacterium and secondly by the signs of periodontitis .…”
Section: Molecular Mimicrysupporting
confidence: 79%
“…All antibody levels were remarkably stable during the 6‐month periodontal treatment. This has also been observed in other studies, whether comprising treatment or not . The levels of antibody to A. actinomycetemcomitans and P. gingivalis are determined primarily by the presence of the bacterium and secondly by the signs of periodontitis .…”
Section: Molecular Mimicrysupporting
confidence: 79%
“…The differences in the neutrophil function between individuals with and without AgP could also be due to a variability in anti-Ltx antibody production and clonality. These antibodies can inactivate Ltx (45), but interindividual differences have not been investigated yet. Moreover, it is likely that other host factors, such as serum components, play a role in enhancing Ltx systemically and, thus, modify the virulence of this toxin (46, 47).…”
Section: Discussionmentioning
confidence: 99%
“…However, the study by Johansson et al. (2016) concluded that the presence and levels of systemic immunoreactivity against Aa leukotoxin are associated with a decreased remission after otherwise successful treatment [78]. These results show that periodontal destruction in periodontitis patients especially JP (aggressive periodontitis) is associated with infection by and an immune response to Aggregatibacter actinomycetemcomitans .…”
Section: The Isolation and Studies Of Super‐leukotoxic Strain Aa Jp2mentioning
confidence: 96%